Corynebacterium ulcerans 0102 carries the gene encoding diphtheria toxin on a prophage different from the C. diphtheriae NCTC 13129 prophage - Sekizuka, Tsuyoshi (BioMed Central, 2012)
BACKGROUND: Corynebacterium ulcerans can cause a diphtheria-like illness, especially when the bacterium is lysogenized with a tox gene-carrying bacteriophage that produces diphtheria toxin. Acquisition of toxigenicity upon phage lysogenization is a common feature of C. ulcerans and C. diphtheriae. However, because of a lack of C. ulcerans genome information, a detailed comparison of prophages has not been possible between these two clinically important and closely related bacterial species. RESULTS: We determined the whole genome sequence of the toxigenic C. ulcerans 0102 isolated in Japan. The genomic sequence showed a striking similarity with that of Corynebacterium pseudotuberculosis and, to a lesser extent, with that of C. diphtheriae. The 0102 genome contained three distinct prophages. One of these, ΦCULC0102-I, was a tox-positive prophage containing genes in the same structural order as for tox-positive C. diphtheriae prophages. However, the primary structures of the individual genes involved in the phage machinery showed little homology between the two counterparts. CONCLUSION: Taken together, these results suggest that the tox-positive prophage in this strain of C. ulcerans has a distinct origin from that of C. diphtheriae NCTC 13129.